Geography, Power, Strategy and Defence Policy: Essays in Honour of Paul Dibb - Ball, Desmond; Lee, Sheryn (ANU Press, 2016)
Paul Dibb AM has had an extraordinary career. He enjoys an international scholarly reputation of the highest order, while at the same time he has done much distinguished public service. He was a pioneer in moving back and forth between posts in government departments, notably the Department of Defence, and academia. He began as a student of Soviet economic geography, and then spent nearly two decades in Australian Defence intelligence, including service as Head of the National Assessments Staff (NAS) in the Joint Intelligence Organisation (JIO) from 1974 to 1978, Deputy Director of JIO in 1978-80, Director of JIO in 1986-88, and Deputy Secretary of Defence (Strategy and Intelligence) in 1988-91, before becoming a Professor in the Strategic and Defence Studies Centre (SDSC) at The Australian National University (where he is now an Emeritus Professor). He has been quite happy to engage in vigorous public debate about important and controversial strategic and defence issues, giving him a high public profile. The contributors include two former Chancellors of ANU, one a former Minister of Defence, and the other a former Secretary of the Department of Defence, a former Chief of the Defence Force (CDF), and other former senior officials, as well as academic specialists in geography, international relations, and strategic and defence studies. 'This would be a high-quality set of essays for any edited volume, but for a festschrift - a genre that sometimes generates uneven collections - this is an exceptional assembly. The individual pieces are very good; together, they have coherence and power.' - Professor Ian Hall, Professor of International Relations, Griffith University